A New Challenge for the Old Excipient Calcium Carbonate: To Improve the Dissolution Rate of Poorly Soluble Drugs - Valeria Ambrogi (MDPI AG, 2023)
Calcium carbonate is an excipient traditionally used in solid dosage forms with several functions such as a diluent, a quick dissolution agent, a buffer and an opacifier. Recently, many other challenges have arisen for calcium carbonate and, among them, the possibility of using it as an excipient for improving the dissolution rate of poorly soluble drugs. As a consequence of their poor solubility in biological fluids, many active ingredients suffer from low and erratic bioavailability when administered by the oral route and thus, many formulation strategies and excipients have been proposed to overcome this problem. Among them, calcium carbonate has been proposed as an excipient for improving dissolution rates. Calcium carbonate has many interesting characteristics, in fact it dissolves quickly in gastric fluid, is inexpensive and is safe. It exists in different polymorphic forms and in porous morphology and recently a porous functionalized calcium carbonate has been proposed as a new excipient. This review is the first overview on the use of calcium carbonate as an excipient for improving drug dissolution rates. The drug loading procedure, the physical characterization of the drug/CaCO3 samples and their dissolution profiles will be described. Moreover, the possible mechanisms of dissolution improvement, such as the presence of the drug in amorphous or polymorphic forms, in small crystals, and the effects of CaCO3 dissolution in acidic medium will be discussed. Different polymorphic forms of calcium carbonate and the presence of porosity and functionalization will be analyzed as well and their effects on dissolution rates will be discussed.